Effects of the probiotic Bifidobacterium animalis subsp. lactis on the non-surgical treatment of periodontitis. A histomorphometric, microtomographic and immunohistochemical study in rats - Ricoldi, Milla S. T.; Furlaneto, Flávia A. C.; Oliveira, Luiz F. F.; Teixeira, Gustavo C.; Pischiotini, Jéssica P.; Moreira, André L. G.; Ervolino, Edilson [UNESP]; De Oliveira, Maricê N.; Bogsan, Cristina S. B.; Salvador, Sérgio L.; Messora, Michel R. (Public Library of Science (PLoS), 2017)
Lactobacillus probiotics have been investigated in periodontitis. However, the effects of the genus Bifidobacterium on periodontitis are hardly known. This study evaluated the effects of the probiotic (PROB) Bifidobacterium animalis subsp. lactis (B. lactis) HN019 as an adjunct to scaling and root planing (SRP) in rats with experimental periodontitis (EP). At baseline, 32 rats were assigned to 4 groups: C (control), PROB, EP-SRP and EP-SRP-PROB. In groups EP-SRP and EP-SRP-PROB, the mandibular first molars of the animals received a ligature. At day 14, the ligatures were removed and SRP was performed. Animals of groups PROB and EP-SRP-PROB were orally administered with 10 mL/day of 109 colony forming units of B. lactis HN019 for 15 days, starting at day 14. Animals were euthanized at day 29. Histomorphometric, microtomographic and immunohistochemical analyses were performed. Microbiological effects of B. lactis on biofilm were also evaluated. Data were statistically analyzed (ANOVA, Tukey; Kruskal-Wallis, Dunn's; Two-tailed t-test; p<0.05). Group EP-SRP-PROB presented reduced alveolar bone resorption and attachment loss when compared with Group EP-SRP (p<0.05). Group EP-SRP-PROB showed significantly fewer osteoclasts, increased expression of anti-inflammatory cytokines and reduced expression of proinflammatory cytokines compared with Group EP-SRP (p<0.05). B. lactis promoted a higher ratio between aerobic and anaerobic bacteria in biofilm samples (p<0.05). B. lactis HN019 may have a role in the treatment of EP in rats, as an adjunct to SRP.